USE OF KB INJECTABLE DEPO MEDROXY PROGESTERONEACETATE (DMPA) IN GEMURUH VILLAGE, KUNDUR DISTRICT KARIMUN REGENCY - Dewi Fitriana; Miralza Diza (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2020)
Background : According to WHO, the number of injectable contraceptive use worldwide is as much as 4,000,000 or about 45%. In the United States, the number of injectable contraceptives is 30%, while in Indonesia, injection contraception is one of the most popular contraceptives. Contraception in Indonesia is the most interested, namely injection contraception at 34.3% (RISKESDAS, 2013). Method : The design that researchers use is a descriptive design that aims to find out the picture. The research data collection was conducted at the Independent Practice Midwives. The population is all active family planning acceptors recorded in the medical record and new acceptors. Sampling was done by using the total sample method. The type of instrument used in this research is a questionnaire, which is a written question addressed to the respondent to be answered. Univariate analysis is used to explain or describe the characteristics of each variable being studied by displaying an overview of the frequency distribution. Result : It is known that the duration of use of DMPA injection contraceptives ≥ 1 year was 27 acceptors (77.1%) while for the duration of use ≤ 1 year there were 8 acceptors (22.9%). Congclusions : It is known that the duration of use of DMPA injection contraceptives ≥ 1 year was 27 acceptors (77.1%) while for the duration of use ≤ 1 year there were 8 acceptors (22.9%).